Motor with external heat supply based on thermo-acoustic effect for an autonomous thermal power plant; Известия Национальной академии наук Республики Казахстан. Серия геологии и технических наук; Vol. 3, № 441 - Mekhtiev A. Ali; Yurchenko A. V. Aleksey Vasilievich; Yugay V. V. Vyacheslav Viktorovich; Alkina A. D. Aliya Dauletkhanovna; Esenzholov U. S. Ulan Serikovich (2020, 2020)
Заглавие с экрана